Think “Big”: Strategizing Post-coronial Revival in India - Gupta, Dipankar (Indian J Labour Econ, 2020)
The pandemic has severely disrupted the economy, but this is also an opportunity to change direction. The distress one saw on the streets of workers leaving cities for their rural homes obviously signals the preponderance of informal labour, low-skilled jobs and lack of economic security. The need, therefore, is to move away from small-scale industrial production to high-technology units which demand sophisticated enterprise, skills and knowledge. This would mean the abandoning of threshold limitations in the labour laws as well as urging MSMEs to grow in size and become competitive enterprises.